The Effectiveness of the Blended Learning Model on Artificial Intelligence Knowledge in Digital Competency Training for Non-Formal Education Teachers - Purnomo, Purnomo; Wahyudin, Uyu; Hadiapurwa, Angga; Alawiyah, Tuti; Pratama, Yolanda Lusiana (Lembaran Ilmu Kependidikan, 2024)
The development of technology, especially artificial intelligence (AI), has great potential to improve the quality of education, including non-formal education in Indonesia. AI-based digital competency training for non-formal education tutors is essential to keeping education relevant to the demands of the digital era, and the blended learning model is considered effective for achieving this goal. This study aims to explore the effectiveness of a blended learning model in improving knowledge of artificial intelligence (AI) in digital competency training for non-formal education tutors in Sukabumi District. This study used a quantitative approach with experimental methods and a pre-experiment design in the form of a one-shot case study, involving 23 trainees. The results showed that the blended learning model was effective in improving the AI knowledge of non-formal education tutors, with a Sig (2-tailed) value of 0.000. In addition to improving tutors' digital competencies, blended learning also offers flexibility and personalization in the learning process, which suits the needs and learning styles of adult participants. This research is expected to provide theoretical and practical contributions to the development of non-formal education in Indonesia as well as a reference in designing training programs that are more effective and relevant to the demands of the digital era. Blended learning, which combines online and face-to-face learning, is an effective model for improving AI knowledge and digital skills for non-formal education tutors while preparing them for future technological challenges.